'How to do things with words': teaching creative writing as performance. Issue 3 (2nd July 2020) - Williams, Paul
ABSTRACT: Using Elbow's model of Expressivism and J. L. Austen's notion of writing as performance, this paper outlines how performative pedagogies of creative writing practice at our university have transformed the creative writing programme. Giving examples from classes I teach, I examine the performative aspects of teaching creativity in first year courses, in collaborative writing workshops, in literature courses for creative writers, and in courses where literary theory is taught, and demonstrate how Creative Writing is taught as a perlocutionary utterance, meaningful only in its effects and contexts, a performative act that becomes itself only in the act of doing.